Rational Cybersecurity for Business The Security Leaders' Guide to Business Alignment - Blum, Dan.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2020)
Use the guidance in this comprehensive field guide to gain the support of your top executives for aligning a rational cybersecurity plan with your business. You will learn how to improve working relationships with stakeholders in complex digital businesses, IT, and development environments. You will know how to prioritize your security program, and motivate and retain your team. Misalignment between security and your business can start at the top at the C-suite or happen at the line of business, IT, development, or user level. It has a corrosive effect on any security project it touches. But it does not have to be like this. Author Dan Blum presents valuable lessons learned from interviews with over 70 security and business leaders. You will discover how to successfully solve issues related to: risk management, operational security, privacy protection, hybrid cloud management, security culture and user awareness, and communication challenges. This open access book presents six priority areas to focus on to maximize the effectiveness of your cybersecurity program: risk management, control baseline, security culture, IT rationalization, access control, and cyber-resilience. Common challenges and good practices are provided for businesses of different types and sizes. And more than 50 specific keys to alignment are included. You will: Improve your security culture: clarify security-related roles, communicate effectively to businesspeople, and hire, motivate, or retain outstanding security staff by creating a sense of efficacy Develop a consistent accountability model, information risk taxonomy, and risk management framework Adopt a security and risk governance model consistent with your business structure or culture, manage policy, and optimize security budgeting within the larger business unit and CIO organization IT spend Tailor a control baseline to your organization$1 (Bs maturity level, regulatory requirements, scale, circumstances, and critical assets Help CIOs, Chief Digital Officers, and other executives to develop an IT strategy for curating cloud solutions and reducing shadow IT, building up DevSecOps and Disciplined Agile, and more Balance access control and accountability approaches, leverage modern digital identity standards to improve digital relationships, and provide data governance and privacy-enhancing capabilities Plan for cyber-resilience: work with the SOC, IT, business groups, and external sources to coordinate incident response and to recover from outages and come back stronger Integrate your learnings from this book into a quick-hitting rational cybersecurity success plan.s
Chapter 1: Executive Overview -- Chapter 2: Identify and Align Security-Related Roles -- Chapter 3: Put the Right Security Governance Model in Place -- Chapter 4: Strengthen Security Culture through Effective Communications and Awareness Programs -- Chapter 5: Manage Risk in the Language of Business -- Chapter 6: Establish a Control Baseline -- Chapter 7: Simplify and Rationalize IT and Security -- Chapter 8: Control Access with Minimal Drag on the Business -- Chapter 9: Institute Resilience Through Detection, Response, and Recovery -- Chapter 10: Create Your Rational Cybersecurity Success Plan -- Glossary of Terms and Acronyms. .
Keywords: Data protection; Data and Information Security